The Analysis Study of Surgical Management and Outcome of Acute Compartment Syndrome: An Orthopaedic and Traumatology Systematic Review - Supriyadi, Agung; Andimapali, Zulfikar; Fitria, Adina (International Medical Journal Corp. Ltd, 2024)
Background: Acute compartment syndrome (ACS) is a serious medical condition that occurs when increased pressure within a closed muscle compartment reduces blood flow and can lead to permanent damage. This systematic review aims to analyze the management strategies, complications, and outcomes of acute compartment syndrome based on current literature. Methods: The review analyzed data from multiple studies, including both prospective and retrospective studies. Results: The analysis included eight studies with a total of 1,019 patients. Factors influencing outcomes in ACS included the time to fasciotomy, fracture status, muscle necrosis indicators, and patient-related factors. Early intervention and appropriate management were associated with better functional outcomes and reduced complications. Conclusion: Effective management of ACS relies heavily on timely intervention and proper post-surgical care. The studies reviewed highlight the importance of early fasciotomy and monitoring for complications to improve patient outcomes.